SOSIALISASI TERAPI KOMPLEMENTER JUS MENTIMUN DALAM MENURUNKAN TEKANAN DARAH PADA ANGGOTA KELUARGA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS PLERED PURWAKARTA - H. Nelson Doloksaribu,; Dina, Dina; Tati Nurhayati, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Hypertension or high blood pressure is a condition where the systolic blood pressure is more than 140 mmHg and the diastolic blood pressure is more than 90 mmHg, if not treated it will increase the risk of heart, brain, kidney disease and stroke. According to WHO (2019) the prevalence of hypertension globally is 22%, the number of people with hypertension in Indonesia reaches 34.11% and always increases every year. Riskesdas, (2018) the prevalence of hypertension in West Java is 39.60%, while the measurement results in Purwakarta Regency are 36.79, the prevalence is greater than the prevalence in Indonesia. In the area of the Plered Health Center, data on outpatient hypertension were found as much as 16.2% (Annual Report of the Plered Health Center, 2022). Researchers aim to provide the application of cucumber juice complementary therapy in lowering blood pressure in family members with hypertension. The research used is a case study which is a type of research that examines problems through case studies consisting of one unit. The single unit that became the case study was analyzed in depth both in terms of the circumstances of the case itself, with the process of implementing cucumber juice complementary therapy in lowering blood pressure in family members with hypertension. The results of research conducted by researchers by conducting research on family members with hypertension, namely Mr. D, when Mr.'s blood pressure was examined. D 170/100 mmhg. Then the researcher gave complementary therapy of cucumber juice for 7 days in the morning and evening as much as 1 glass (200cc), after being given cucumber juice therapy for 7 days the results showed a decrease in blood pressure to 150/80 mmhg. After nursing intervention it can be concluded that The application of cucumber juice therapy is very effective in reducing blood pressure and has been proven by researchers to reduce blood pressure before and after being given cucumber juice therapy